2022
DOI: 10.1590/s0104-12902022210649pt
|View full text |Cite
|
Sign up to set email alerts
|

O impacto da pandemia de covid-19 na assistência à saúde mental de usuários de álcool nos Centros de Atenção Psicossocial

Abstract: Resumo A preocupação com o consumo prejudicial de álcool está na interseção da pandemia com a saúde mental. Mudanças nos padrões de consumo durante a crise sanitária têm sido documentadas no Brasil e internacionalmente. Este estudo avaliou o impacto da pandemia nos procedimentos a usuários de álcool no Brasil, por meio dos registros dos Centros de Atenção Psicossocial (CAPS). Selecionaram-se dados de janeiro de 2019 a dezembro de 2020, com discriminação por macrorregião geográfica, sexo, idade e raça/cor. Real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Finally, we highlight the pandemic period in Brazil, in particular the mortality rates due to intentional self-poisoning by medicines in 2021 and 2022, which were, respectively, 1.8 and 2.6 times higher than those of 2003. In Brazil, the pandemic year of 2021 was the most critical in terms of mortality ( 53 ), and was marked by deep uncertainties and suffering ( 54 ), increased self-medication ( 55 ) and a decrease in the regular supply of mental health services ( 56 , 57 ), as well as evidence of increased domestic violence against women ( 58 ). This may be potentially related to the increased risk of intentional self-poisoning by medicines in this subgroup, mainly psychotropic medicines, as was the case in Croatia during the COVID-19 pandemic, for example ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we highlight the pandemic period in Brazil, in particular the mortality rates due to intentional self-poisoning by medicines in 2021 and 2022, which were, respectively, 1.8 and 2.6 times higher than those of 2003. In Brazil, the pandemic year of 2021 was the most critical in terms of mortality ( 53 ), and was marked by deep uncertainties and suffering ( 54 ), increased self-medication ( 55 ) and a decrease in the regular supply of mental health services ( 56 , 57 ), as well as evidence of increased domestic violence against women ( 58 ). This may be potentially related to the increased risk of intentional self-poisoning by medicines in this subgroup, mainly psychotropic medicines, as was the case in Croatia during the COVID-19 pandemic, for example ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that nearly 93,000 people died by suicide annually between 2015 and 2019 in the Americas (PAHO, 2022). Apart from this remarkable mortality pattern several studies have showed that the pandemic is having burdensome repercussions on mental health, increasing anxiety and depression, coupled with the severe disruption of mental health services and deepening inequalities, mainly in Latin America and Caribbean countries (Gerbaldo & Antunes, 2022; Oliveira et al, 2023; Tausch et al, 2022).…”
Section: Introductionmentioning
confidence: 99%